The impact of financial restatement on firm value: Malaysian evidence / Norazzie Md Zin - Md Zin, Norazzie (2013)
The purpose of this study is to examine the relationship between financial restatement and firm value in Malaysian public listed firms. In addition, it tries to assess the moderating effects provided by corporate governance mechanisms on the relationship of financial restatements and firm value. The study used financial restatements as independent variable and firm value as dependent variable. The measurement used to measure firm value is Tobin’s Q. The moderating variable used in this study is corporate governance mechanism. The governance variables involved are board size, board independence, CEO duality, family ownership, institutional ownership, political connection, and audit committee having financial expertise. Due to limited previous research conducted on financial restatement in Malaysian firms, this dissertation attempts to fill the gap. It is hypothesised that in general, financial restatement has negative impact on the firm value. In order to examine the findings, the study covers the period of 2005 until 2011 and involved 142 public listed companies in Bursa Malaysia with financial restatements. The data is analysed using a quantitative method that employed by SPSS. Then multiple regressions are used to estimate the relationships proposed in the hypotheses. The finding reveals that financial restatements do adversely impact firm value. The results show that financial restatements negatively and significantly affect firm value. This indicates that financial restatements signal a red flag of the firm’s credibility, and that management is doing something wrong with their investment, which leads them to issue a restatement of the financial statement. In term of moderating variables, the regression model identified that the interaction between financial restatement and family ownership is negatively associated with firm value, in addition, this study finds that the interaction between financial restatement and institutional ownership is positively and significantly associated with firm value. This indicates that the active or increased involvement of institutional ownership directly increases the value of the restating firm. This is because investors see institutional investors as their watchdog and a means for promoting the restoration of investor confidence. Other moderating variables are found to be not significant with Tobin’s Q.As a conclusion, in Malaysian context, this study established that financial restatement has negative impact on firm value.